Pengaruh Penggunaan CMC (Carboxymethyl cellulose) Terhadap Sifat Organoleptik Kue Pia Gorontalo Dengan Bahan Baku Tepung Jagung - Christy Sakendatu; Dekie Rawung; Lucia Mandey (COCOS, 2016)
ABSTRACTCorn is a main commodity of Gorontalo Province and often become typical culinary from Gorontalo. But processing of pia is use 100% wheat flour as main ingredient, so how to make a pia use as much as possible corn flour become a basic of this research with CMC as fastener. The benefit of this research to produce pia from corn flour that can be a typical culinary of Gorontalo. This research is use CMC with 1%, 2%, and 3% consentration in mix flour (corn flour 80% and wheat flour 20%) to test receptivity of corn pia by organoleptic test consist of texture, color, taste and to analyze chemical character of corn pia. According to the sensory analyzing data, corn flour can be processed into pia. Addition of 2% CMC produces pia with most preferably through a test based on organoleptic test and in different test sample had better color than control but texture and mothfeel same as control.Keywords : Pia, Corn Flour, CMC